2002
DOI: 10.1007/s102670200021
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the preservation of fungus stock cultures by deep-freezing

Abstract: Recovery of 66 fungus stock cultures including Oomycota, Zygomycota, Ascomycota, Basidiomycota, and mitosporic mycetes were examined after cryopreservation. Almost all the stock cultures remained viable when the mycelia that had grown over the sawdust medium containing 10% glycerol as the cryoprotectant (65% moisture content, W/W) were frozen rapidly at Ϫ85°C and then allow to thaw naturally at room temperature. Test stock cultures were preserved for more than 10 years by this preservation method without any p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 4 publications
0
27
0
7
Order By: Relevance
“…Após esse período, ocorre a sua degeneração natural, que perde a capacidade de formar novos descendentes (Kitamoto et al, 2002). Cita-se como exemplo o fungo C. cladosporioides, que tem como temperatura mínima de crescimento -4ºC, e temperatura ótima, 22ºC.…”
Section: Discussionunclassified
“…Após esse período, ocorre a sua degeneração natural, que perde a capacidade de formar novos descendentes (Kitamoto et al, 2002). Cita-se como exemplo o fungo C. cladosporioides, que tem como temperatura mínima de crescimento -4ºC, e temperatura ótima, 22ºC.…”
Section: Discussionunclassified
“…Kitamoto et al (2002) grew cultures over SDM (65% moisture W/W) with 10% glycerol as the cryoprotectant and then rapidly froze them at 285uC and tested viability by inoculating on PDA; several zygomycete cultures remained viable for 20 mo. These and other methods are discussed in detail by Fennell (1960), Jong and Birmingham (2001), and Nakasone et al (2004).…”
Section: Maintenancementioning
confidence: 99%
“…Cryopreservation at -70°C is more effective than at -20°C but it requires expensive equipment. Kitamoto et al [11] report a long-term cryopreservation protocol for some species of basidiomycetes using ultrafreezers at -80°C. However, Ryan et al [3] reported that no method can be universally applied to all fungi and that while some species are difficult to preserve, others can be preserved by almost any method.…”
Section: Introductionmentioning
confidence: 99%